Prototype Implementation of It Business VPS and Web Hosting Services as a Research Laboratory for Bina Darma University - Suryayusra; Alfarizhi, Reyhan Achmad; Fatoni; Tamsir Ariyadi; Maria Ulfa (INOVTEK Polbeng - Seri Informatika, 2024)
In today's digital era, the need for flexible and reliable IT infrastructure is increasing, especially in the education and business sectors. This research aims to develop a prototype of VPS (Virtual Private Server) and web hosting services as a research laboratory as well as IT business services at Bina Darma University. This service is designed not only to support student research, but also as an IT business model that offers hosting solutions that can be customized according to customer needs. The main objective of this research is to create a digital infrastructure solution that allows students to learn and practice in server management and hosting directly, while developing a market-ready IT hosting business service. This prototype is expected to provide a stable and secure research environment, as well as a potential IT service business model. This research utilizes an action research methodology, which involves a cycle of planning, development, performance testing, and evaluation. Testing includes performance, security, and operational cost analysis, as well as case studies of VPS service implementation in academic and business environments. Evaluation was conducted based on feedback from service users. The results of the research are expected to have a significant impact on the development of IT hosting businesses in academia and industry, as well as improving students' practical skills in digital infrastructure management.